(untitled) (Bangladesh Veterinarian, 2016)
The effect of GnRH analogue (gonadorelin) was studied on the fertility of 35 postpartum anoestrus zebu cows and their crosses (Friesian, Sahiwal, Sindhi). Age (4-15 years), body weight (125-375 kg), body condition score (1.5-3; 1-5 scale), parity (1-9), postpartum intervals (4-12 months) of the cows were recorded. Oestrus was synchronized with two injections of PGF2-? analogue (Luprostinol, 15 mg) intramuscularly (i.m.) 10 days apart. The cows were divided into Group I (n = 11), Group II (n = 12) and Group III (n = 12). In Group I, 8 cows with oestrus were inseminated without gonadorelin treatment. In group II, 6 cows in oestrus were treated with gonadorelin (0.25 mg) i.m. just prior to insemination. In group III, 3 days after the second injection of luprostinol, cows with smooth ovaries were treated with gonadorelin followed by luprostinol injection 9 days later, which resulted in oestrus in 8 of the 12 cows, which were inseminated. Cows without oestrus signs were inseminated at fixed-time (72 and 96 hours after the last luprostinol injection). In group I, II and III, 5, 6 and 8 cows became pregnant, respectively (P>0.05). More cows became pregnant at observed oestrus (68.2%) than at fixed-time insemination (30.8%; P<0.05). Insemination in observed oestrus is more effective than at fixed-time. GnRH analogue may have favourable effect on the induction of oestrus by PGF2-? analogue. Bangl. vet. 2014. Vol. 31, No. 2, 60-69